Academic Diaspora and Internationalization: UK-based Turkish Academics - Durak, Tugay (International Higher Education, 2023)
With rising numbers of international academics, the discussions around the possible benefits that they provide to their fellow nationals and home country are well documented in the literature. However, there has been little attention as to how their diasporic engagements reinforce the internationalization of higher education while supporting fellow nationals. Taking UK-based Turkish academics as an example, this article sheds light on the relationship between the academic diaspora and the internationalization of higher education.